Amorpha fruticosa – A Noxious Invasive Alien Plant in Europe or a Medicinal Plant against Metabolic Disease? - Kozuharova, Ekaterina; Matkowski, Adam; Woźniak, Dorota; Simeonova, Rumiana; Naychov, Zheko; Malainer, Clemens; Mocan, Andrei; Nabavi, Seyed M.; Atanasov, Atanas G. (Frontiers in Pharmacology, 2017)
Amorpha fruticosa L. (Fabaceae) is a shrub native to North America which has been cultivated mainly for its ornamental features, honey plant value and protective properties against soil erosion. It is registered amongst the most noxious invasive species in Europe. However, a growing body of scientific literature also points to the therapeutic potential of its chemical constituents. Due to the fact that A. fruticosa is an aggressive invasive species, it can provide an abundant and cheap resource of plant chemical constituents which can be utilized for therapeutic purposes. Additionally, exploitation of the biomass for medicinal use might contribute to relieving the destructive impact of this species on natural habitats. The aim of this review is to provide a comprehensive summary and systematize the state-of-the-art in the knowledge of the phytochemical composition and the potential of A. fruticosa in disease treatment and prevention, with especial emphasis on diabetes and metabolic syndrome. Also reviewed are aspects related to potential toxicity of A. fruticosa which has not yet been systematically evaluated in human subjects.